2010
DOI: 10.1007/s10750-010-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Food quantity shapes life history and survival strategies in Daphnia magna (Cladocera)

Abstract: Life history and demographic responses to different food regimes were investigated in three clones of Daphnia magna. Green alga Scenedesmus obliquus served as food source and was given in five amounts, which covered the range from near threshold to excess food concentrations, from 0.05 through 0.15, 0.5, 1.5 to 4.5 mg C l -1 . The animals were kept under given food regime from first instar until their natural death. Food regime had a significant effect on Daphnia survival, which was shortest under the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
4
25
0
Order By: Relevance
“…Such a trade-off is commonly observed in Daphnia (Glazier & Calow, 1992;Dudycha, 2003). For example, Pietrzak et al (2010) found that investments in early reproduction were costly in Daphnia and result in a shortened lifespan. In our experiment a similar pattern was observed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Such a trade-off is commonly observed in Daphnia (Glazier & Calow, 1992;Dudycha, 2003). For example, Pietrzak et al (2010) found that investments in early reproduction were costly in Daphnia and result in a shortened lifespan. In our experiment a similar pattern was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Food limitation has been shown to decrease growth and reproduction while increasing longevity (Pietrzak et al, 2010). Here, we investigate the effects of variation in food availability on host-microbiota interactions in Daphnia by comparing symbiotic with germ-free hosts raised in environments with different levels of food availability.…”
Section: Introductionmentioning
confidence: 99%
“…Diet quality has been shown to have a mixed impact on the survivorship of other crustaceans, such as amphipods, whose survivorship on diets that mix high-and low-quality food sources varies widely depending on the species (Cruz-Rivera & Hay 2000a,b), and diet quantity is inversely correlated with longevity in a variety of species (e.g. Lawler et al 2008, Pietrzak et al 2010. Alternatively, the inclusion of nitrogen-rich animal tissue in its diet significantly improved the reproductive investment and physiological condition of Aratus pisonii.…”
Section: Discussionmentioning
confidence: 99%
“…This can again be linked to an energy allocation perspective. When nutrients are limiting, organisms allocate energy towards increased reproduction and growth rate, but at the cost of survival (Boggs 2009;PietrzaK et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the keystone grazer Daphnia (Crustacea, Branchiopoda) requires a sufficient amount of P to invest in P-rich ribosomal RNA (rRNA), which is needed for protein synthesis and growth (eLser et al 2000(eLser et al , 2003. Nutrient deprivation will also affect trade-offs between life history traits, e.g., prolonging life span, but at the cost of reproduction (Boggs 2009;PietrzaK et al 2010).…”
Section: Introductionmentioning
confidence: 99%